Seasonal incidence of fruit borer, Helicoverpa armigera (Hub.) in tomato in relation to weather parameters - Singh, Narendra; Dotasara, S. K.; Jat, Sanwar Mal; Naqvi, A. R. (Annals of Agricultural Research, 2018)
A field experiment was conducted at farm of Agricultural Research station, Swami Keshwan and Rajasthan Agricultural University, Bikaner, during the 2013-14, rabi season, to study seasonal incidence of tomato fruit borer, Helicoverpa armigera. Tomato fruit borer, H. armigera is a well known polyphagous insect. The larvae feed on the leaves and bore into fruits, thereby causing severe damage to the crop and significant losses in yield. Besides tomato, it is a regular pest of chickpea and cotton. The incidence of fruit borer started in the last week of December on tomato. The population lowered down upto 3rd SMW (Standard Meteorological Week) and thereafter, population increased but fluctuating trend was recorded upto 9th SMW. The larval population increased and reached to peak in 12th SMW. Thereafter, it’s population decreased gradually and negligible population was recorded upto second week of April. A significant positive correlation was observed between pest population and maximum and minimum temperature, whereas, it was non-significant positive with average relative humidity. A non-significant negative correlation was computed between pest population and total rainfall.